Disease facts: pemphigus foliaceus in the dog and cat. Issue 8 (7th October 2013) - Craig, Mark
<x xml:space="preserve">Abstract</x> Pemphigus foliaceus is one of the most frequently occuring auto‐immune skin conditions in the dog and cat. It is characterised by a pustular, crusting dermatosis and affects mainly middle‐aged‐to‐older dogs. In this article, veterinary dermatologist Mark Craig presents key 'disease facts' for the practicing veterinarian on the most common condition of the pemphigus complex in the dog and cat. Clinical features, diagnostic steps, treatment options and prognosis will be discussed.